if f(x)=2x-3 and fg(x)=2x+1,find g(x)
You should notice that the composition of the functions f and g is a linear function.
You need to remember how to compose two functions such that:
`(fog)(x) = f(g(x))`
Since `f(x) = 2x - 3` , you should substitute g(x) for x such that:
`f(g(x)) = 2g(x) - 3`
The problem provides the information that `f(g(x)) = 2x+1` , hence, you should set the equations 2g(x) - 3 and 2x+1 equal such that:
`2g(x) - 3 = 2x + 1 =gt 2g(x) = 2x + 1 + 3`
`2g(x) = 2x + 4`
Dividing by 2 yields:
`g(x) = x + 2`
Hence, evaluating the function g(x) under the given conditions yields `g(x) = x + 2` .
check Approved by eNotes Editorial